PELAYANAN REHABILITASI BADAN NARKOTIKA NASIONAL PROVINSI JAWA TIMUR TERHADAP PENYALAHGUNA NARKOBA - Seto Michiko (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2016)
The drugs trafficking abuse and circulation has show increasing and tends to destroy the future generation of the nation, the government policy was appointed permanently the national narcotics derpartement (BNN) as a government department non ministry to prevent and against illegal drugs trafficking in Indonesia.The problem that author want to describe in this thesis is how rehabilitations services and implementation to drugs addict is going to do by National Narcotics Department (BNN) in province of East Java.The National Narcotics Department do the public service in many programs, the rehabilitation is doing by a prosedur and determined by number of people who will serve out rehabilitation at the pointed place by the national narcotics department. But in implementation of doing the rehabilitation there is obstacles that hamper the rehabilitation fluency of the national narcotics rehabilitations in province of East Java.Keywords: Drugs, public services, rehabilitations